Peningkatan Keterampilan Menghafal Bacaan Salat di Musala Nurul Hidayah Lubuk Agung Menggunakan Metode Drill dan Media PowerPoint - Ariani, Gina Oktavia; Putra, Rido (YASIN, 2025)
This study is motivated by the fact that out of 60 students at Musala Nurul Hidayah Lubuk Agung, 40 students, including those in third, fourth, and even sixth grade of elementary school, still have not memorized the prayer recitations. The objective of the study is to improve students’ memorization skills of prayer recitations through the application of the drill method and PowerPoint media. This research is a Classroom Action Research (CAR) using a qualitative approach, conducted over two cycles, each consisting of two sessions. Data were collected through memorization tests of prayer recitations involving all students. The results indicate a significant increase from the initial (pre-cycle) condition of 56%, to 73.5% in the first cycle, and further to 93.1% in the second cycle. This improvement shows that students’ memorization skills of prayer recitations had reached a good category by the end of the second cycle. These findings support the hypothesis that using the drill method and PowerPoint media is effective in enhancing the ability to memorize prayer recitations. This study provides practical contributions for educators in selecting appropriate teaching strategies and serves as a basis for further research focusing on different contexts or variables.